2021
DOI: 10.1021/acs.jproteome.1c00805
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnostic Ability of Human Complement Factor B in Pancreatic Cancer Is Partly Linked to Its Potential Tumor-Promoting Role

Abstract: Although plasma complement factor B (CFB, NX_P00751), both alone and in combination with CA19-9 (i.e., the ComB-CAN), previously exhibited a reliable diagnostic ability for pancreatic cancer (PC), its detectability of the early stages and the cancer detection mechanism remained elusive. We first evaluated the diagnostic accuracy of ComB-CAN using plasma samples from healthy donors (HDs), patients with chronic pancreatitis (CP), and patients with different PC stages (I/II vs III/IV). An analysis of the area und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…To our knowledge, this represents the first observation of quantitatively differential expression of proteotypic peptide fragments of CFB (seq 2) present in the plasma of PDAC patients across different disease stages, consistent with the conventional ELISA assay results. 36,37 These findings also provide potential insights into changes in the ACP activity in this cancer across different disease stages.…”
Section: Absolute Quantification Of Cfb Peptides Present In Plasma By...mentioning
confidence: 77%
See 4 more Smart Citations
“…To our knowledge, this represents the first observation of quantitatively differential expression of proteotypic peptide fragments of CFB (seq 2) present in the plasma of PDAC patients across different disease stages, consistent with the conventional ELISA assay results. 36,37 These findings also provide potential insights into changes in the ACP activity in this cancer across different disease stages.…”
Section: Absolute Quantification Of Cfb Peptides Present In Plasma By...mentioning
confidence: 77%
“…56−58 Specifically, PDAC cell lines harboring KRAS mutation have been found to exhibit higher expression levels of CFB, shedding light on the oncogenic activity of CFB within the context of KRAS mutation. 13,37 Furthermore, it is known that KRAS mutation positively regulates the expression levels of complement factors and their regulator (s), including C3b, CFB, CFH, and AM (Figures 3 and 7). For the AM's role in carcinogenesis, previous studies have indicated that tumor-associated macrophages (TAMs) induce AM synthesis, which, in turn, promotes cancer cell growth, suggesting a synergistic role of AM and TAMs in the malignant development of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations